The landmark for removal of sialoliths using sialendoscopy alone in parotid gland sialolithiasis. Issue 2 (April 2018) - Kondo, Norio; Yoshihara, Toshio; Yamamura, Yukie; Kusama, Kaoru; Sakitani, Eri; Seo, Yukako; Tachikawa, Mayako; Kujirai, Keiko; Ono, Erika; Maeda, Yasuyo; Nojima, Tomohito; Tamiya, Akiko; et al.
Abstract: Objective: To assess the general guidelines for removal of sialoliths in parotid gland sialolithiasis using sialendoscopy alone. Methods: We analyzed 34 sialoliths treated using sialendoscopy in 26 patients with parotid gland sialolithiasis. We divided the Stensen's duct and parotid gland into for parts using computed tomography findings: (A) front of the masseter, (B) anterior and lateral to the center (anterolateral) of the masseter, (C) posterior and lateral to the center (posterolateral) of the masseter, (D) behind of the masseter. The location and size of each sialolith was assessed. Results: The removal rates of sialoliths in the different locations by sialendoscopy alone were as follows: front of the masseter, 68.8%; anterolateral of the masseter, 60.0%; posterolateral of the masseter, 0%; and behind of the masseter, 33.3%. The removal rate using sialendoscopy alone was significantly higher in the sections anterior to the center of the masseter than in those posterior to the center of the masseter (66.7% [14/21] vs. 20.0% [2/10]; P = 0.019). The size of the sialolith was not correlated to the removal rate by sialendoscopy alone. Conclusion: Sialoliths of the parotid gland located in positions anterior to the center of the masseter are significantly easier to remove by sialendoscopy alone. The center of the masseter is a general landmark for removal of sialoliths from the parotid gland using sialendoscopy alone. The size of the sialolith is not correlated with removal, except rare huge sialoliths.